Pemberdayaan kader dalam edukasi pemberian ASI dan menyusui pada ibu hamil di wilayah Ilir Barat II - Ardesy Melizah Kurniati; Aryani Aziz; Eka Handayani Oktharina; Septi Purnamasari; Syarif Husin; Naila Nirmala Puspitasari; Corinna Faustina; Putri Salsabila (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Exclusive breastfeeding is essential for maternal and infant health, yet its coverage remains low in several regions. This community service activity aims to evaluate the effectiveness of community-based counseling in improving knowledge among Posyandu cadres and pregnant women. The activity involved 11 cadres and 32 pregnant women in Ilir Barat II using pretest, counseling, discussion, simulation, and post-test approaches. Results showed an increase in participants' knowledge scores, with the cadres' median pretest score improving from 12 (8–18) to 18 (14–19), and pregnant women’s scores rising from 8.6 (2–15) to 17 (13–20). The PRECEDE-PROCEED model was applied to identify predisposing factors through IPTEKS-based education, enabling through simulations, and reinforcing through cadre support. Community-based counseling proved effective in enhancing participants' knowledge, though the changes were not entirely significant. This program has the potential to be replicated in other areas to improve exclusive breastfeeding coverage in Indonesia.